Design of Lifting Tool and Pressing Table at Tofu Factory X Considering to the Operator's Work Posture - Yohannes Alvin Wijaya; Winda Halim (School of Industrial and System Engineering, Telkom University, 2023)
The X Tofu Factory on of tofu factory located in Sumedang City. Based on the results of aninterview with the owner of the X Tofu Factory, Owner stated that there were several problemsthat occurred at the X Tofu Factory. The main problem that occurs is the frequent occurrence ofMusculoskeletal Disorder complaints caused by poor work posture and inadequate physicalfacilities. The purpose of this study was to design work aids to be used to lifting load at grindingwork stations and posture when work at pressing station. Theories are used include designthinking for the design of work aids at milling work stations, Rapid Entire Body Assessment(REBA) to determine the risk score of work postures, Wisha Lifting Calculator (WLC) todetermine the limiting index of lifting activities, and anthropometry for designing physicalfacilities in the form of a tofu moulding table. Data collection was carried out in the tofuproduction area by taking tool size data, the Nordic Body Map (NBM) questionnaire, and actualanthropometric data. From the results of data processing and analysis of the problems above, theresearchers proposed work aids to reduce REBA and Wisha scores, and physical facilities thatwere adjustable in height operator's anthropometric data.